Potential analysis of multidisciplinary biopsychosocial rehabilitation for patients with chronic low back pain / Potentialanalyse der multidisziplinären biopsychosozialen Rehabilitation für Patienten/-innen mit chronischen Rückenschmerzen - Schüßler Beate; Abel Angsar; Holzer Milena; Meise Ruth; Voigt-Radloff Sebastian; Schäfer Axel (Sciendo, 2017)
The prevalence of low back pain ranges from 74 to 85%, almost everybody in Germany suffers from low back pain once in his or her life. The recurrence rate within twelve months is 62%, which often leads to inability to work and reduction in earning capacity. The rate of chronic manifestation of low back pain is 5%. Subsequent loss of mobility and functional disability lowers quality of life and participation in private life and at work.